DIGITAL DISINFORMATION AND CRISIS OF LEGITIMACY: CHALLENGES AND PERSPECTIVES OF BRAZILIAN ELECTORAL LAW (CIPEEX, 2025)
Introduction: In 2022, the Superior Electoral Court (TSE) enacted Resolution No. 23.714, which addresses the fight against disinformation, adopted with the aim of mitigating the effects of the spread of “fake news,” by imposing sanctions on those who disseminate untrue content. This measure seeks to ensure the transparency of elections and protect trust in the institutions responsible for managing the electoral process.Objective: The objective of this study is to present the problems currently faced by the Electoral Justice and analyze their impacts on the future of Brazilian legislation.Method: The methodology adopted in this research was a bibliographic review, carried out through consultation of scientific articles and legal websites, published between 2020 and 2023.Results: The electoral period between 2018 and 2022 was marked by the dissemination of illegitimate content that affected the credibility of the electoral process and the image of several candidates. As a result, the instability generated by the circulation of such information, often with the intent of damaging opposing candidacies, culminated in the events of January 8, 2023, with the invasion of the headquarters of the Three Branches of Government. The lack of credibility in the election results, aggravated by the spread of fake news, compromised the integrity of the electoral process. As a consequence of legislative gaps, the creation of specific norms for the digital context became urgent.Conclusion: Therefore, electoral legislation needs constant updates to deal with the impact of technology. Legislative reforms and interprofessional collaboration will be able to address the gaps arising from outdated rules.
Keywords: disinformation; electoral justice; fake news